Analisa Hazard Navigation Map terhadap Resiko Tubrukan Kapal - Rivai, Haryanti; Farapahlefi, Andi Saiyid; Baharuddin, Baharuddin; Zulkifli, Zulkifli; Rahimuddin, Rahimuddin (Jurnal Penelitian Enjiniring, 2019)
Hazard Navigation Map Analysis on Risk of Ship Collision (Case Study: Water way of Port of Makassar). Accidents in Indonesian Marine Transportation should be a concern of all parties that effect accumulation of dangers score from some factors, based on data from the KNKT (Komite Nasional Keselamatan Transportasi) ship accident investigation report. The collision cases were among the highest in recent years and most collisions occurred in the harbor area. The purpose of this study was to analyze and compile the danger score criteria that affect ship collision risk from several factors consisting of ship condition factors, human factors, environmental factors, machinery factors, and management factors. The research was conducted with the AHP (Analytical Hierarchy Process) method. AHP method is used to create a model of the problem that has no structure, applying to problems measurable (quantitative), as well as problems that need an opinion from expert or a complex situation or do not have a frame work. AHP stages are decomposition problem, assessment and comparison of the elements of the synthesis in priorities. The result showed that human factor is the highest priority that affects the value of danger score in Makassar Port to the value of 0.395 or 39% and management factors with the lowest priority value of 0.073 or 7.3%. While the total value of danger score in Makassar Port with AHP method is 196.95 which means at the level of a fairly safe.